Two new species of the planthopper genus Deferunda Distant from China (Hemiptera: Fulgoromorpha: Achilidae), with the first description of the male of Deferunda acuminata Chou & Wang - Lv, Shasha; Chen, Xiangsheng; Long, Jiankun (Zootaxa, 2023)
Two new species of the genus Deferunda Distant, 1912, D. dentata sp. nov. and D. interanea sp. nov. from China (Shandong and Hainan provinces, respectively), are described and illustrated, bringing the total number of species within the genus to 17. The male genitalia of D. acuminata Chou & Wang, 1985 is described and illustrated for the first time. Geographical information, a checklist and key to all known species of Deferunda are provided.